FOSTER OR INSPIRE When teaching becomes a driving force for student entrepreneurship - Abdelbast WADDAD; Mohamed SABRI (International Journal of Scientific Research and Innovative Studies, 2026)
In an increasingly changing socio-economic context, Morocco is facing high unemployment, particularly among graduates, highlighting a mismatch between education and the needs of the labour market. Indeed, the disconnect between the skills acquired at university and the demands of the professional market underscores the need for more appropriate training (Benamar et al., 2016). In this context, student entrepreneurship is emerging as a promising alternative for employability. Promoting university initiatives to stimulate entrepreneurial intent among students could serve as a lever for improving career prospects. This interaction between universities and entrepreneurship goes beyond the simple notions of business creation. Universities have gradually evolved to become key players in promoting entrepreneurial spirit, thereby fostering encounters between universities and entrepreneurs. It is therefore essential to understand the institutional role of universities in promoting a culture of entrepreneurship among their students. Similarly, the involvement of teachers through the use of innovative teaching methods can have a positive effect on students' entrepreneurial intentions. In this study, we will attempt to examine the perceptions of students at Cadi Ayyad University (UCA) regarding the impact of university initiatives on the development of entrepreneurial intentions among students, particularly the role of teachers and the effectiveness of the teaching methods used. Keywords: University, Entrepreneurship, Student, Entrepreneurial intention, Teacher, Teaching methods used. Received Date: February 22, 2026 Accepted Date: March 14, 2026 Published Date: April 02, 2026 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/587